2009
DOI: 10.1111/j.1471-0528.2009.02320.x
|View full text |Cite
|
Sign up to set email alerts
|

Current status of contraceptive use among rural married women in Anhui Province of China

Abstract: Objectives This study aims to explore the current status of married women in regard of their use of contraceptive methods (permanent methods versus non-permanent methods) and to find out factors that affect the use of contraceptive methods in rural areas of Anhui Province of China.Design Survey.Setting Anhui, China.Population A total of 53,652 married women aged 18-49 years.Methods A multistage probability sampling method was used to identify a representative sample of 53,652 married women aged 18-49 years. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…The range of contraceptive use detected in the present survey was consistent with earlier studies in China [10][11][12]. In the current study, sterilization and IUDs were the 2 most popular methods, followed by condoms and pills.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The range of contraceptive use detected in the present survey was consistent with earlier studies in China [10][11][12]. In the current study, sterilization and IUDs were the 2 most popular methods, followed by condoms and pills.…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of the study population was 38.09 ± 7.43 years, which was consistent with previous studies in China [10,11]. The mean age at marriage was 21.99 ± 1.85 years.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…They have observed that the use of contraceptive methods was associated with age, education, parity, frequency of sexual intercourses in a month, and contraceptive knowledge of rural married women. [10] These fi ndings agree with those in the present study. Hogan and Biratu have studied the effect of education and socioeconomic status on the use of contraceptives in southern Ethiopia.…”
Section: Manovasupporting
confidence: 94%
“…Contraceptive use in China has steadily increased since the 1-child policy was introduced in the late 1970s, with all-method prevalence at 86.9% in 2002 [1]. Although usage is high, the most popular contraceptive methods vary by region and age group [1,2], with recent studies indicating that such differences in usage may be attributable to lack of availability and information about specific methods [13].…”
mentioning
confidence: 99%